THE SPIRIT OF FEMINISM AGAINST WOMEN NEGATIVE STEREOTYPES IN VERONICA ROTH’S DIVERGENT - AINUN, HILDA NUR (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Divergent, Feminism, Gender, Women Negative Stereotypes.Gender is social and cultural construction about the differences of the roles and opportunities between men and women which occur in society. Gender often causes inequality between man and woman which usually disadvantages woman because of the negative stereotypes that exist in the society. The writer conducted a study on Divergent novel to analyze the portrayal of female characters countering negative stereotypes that exist in their society.Sociological approach is used in this research related with the context in the society. Feminism theory is applied in this study to analyze the data which mainly about the struggle of female characters in the society.This study reveals that the female characters in the Divergent novel do not fit the negative stereotypes that are labelled on them. The portrayal of women characters are considered as the picture of strong, brave, and intelligent women who has important contribution to the society. The women characters proves that they have courage and bravery, for example they can make decision over themselves and willing to sacrifice their life for others whom they love. Second, the women characters are depicted as brilliant which makes men feels threatened and intimidated. Third, the women characters depicted has physically, mentally,and emotionally strong that makes men feels threatened and the last, the women characters depicted as having important role to contribute to the social development by helping others.In conclusion, the women characters in this novel prove that women do not fit the stereotypes that are attributed by the society. In this novel, the women characters are considered as the portrayal of strong, brave, and intelligent women who also has important contribution to the society.The writer suggests the next researchers to use different approach or theories such as Psychology or Marxism to analyze the novel. The first theory can be used to understand the characters and their psychological development. Meanwhile the second theory can be used to observe the social class struggles within the society in the novel.